Effects of Hyperglycemia on Vascular Smooth Muscle Ca2+ Signaling. (21st June 2017) - El-Najjar, Nahed; Kulkarni, Rashmi P.; Nader, Nancy; Hodeify, Rawad; Machaca, Khaled
Abstract : Diabetes is a complex disease that is characterized with hyperglycemia, dyslipidemia, and insulin resistance. These pathologies are associated with significant cardiovascular implications that affect both the macro- and microvasculature. It is therefore important to understand the effects of various pathologies associated with diabetes on the vasculature. Here we directly test the effects of hyperglycemia on vascular smooth muscle (VSM) Ca 2+ signaling in an isolated in vitro system using the A7r5 rat aortic cell line as a model. We find that prolonged exposure of A7r5 cells to hyperglycemia (weeks) is associated with changes to Ca 2+ signaling, including most prominently an inhibition of the passive ER Ca 2+ leak and the sarcoplasmic reticulum Ca 2+ -ATPase (SERCA). To translate these findings to the in vivo condition, we used primary VSM cells from normal and diabetic subjects and find that only the inhibition of the ER Ca 2+ leaks replicates in cells from diabetic donors. These results show that prolonged hyperglycemia in isolation alters the Ca 2+ signaling machinery in VSM cells. However, these alterations are not readily translatable to the whole organism situation where alterations to the Ca 2+ signaling machinery are different.